Deformability of transfused red blood cells is a potent determinant of transfusion-induced change in recipient's blood flow - Barshtein, Gregory; Pries, Axel R.; Goldschmidt, Neta; Zukerman, Ayelet; Orbach, Ariel; Zelig, Orly; Arbell, Dan; Yedgar, Saul (Microcirculation (New York, N.Y. 1994), 2016)
Objective There is a growing concern regarding the risks in the transfusion of PRBC, as numerous studies have reported negative transfusion outcomes, including reduced blood perfusion. In search of this phenomenon's mechanism, the effect of PRBC deformability, a major determinant of blood flow, on transfusion outcome was explored. Methods The effect of PRBC deformability was examined by the transfusion‐induced change in recipients’ ∆SBF, in β‐TM patients, who are routinely treated with lifelong frequent transfusions. SBF was determined using a laser Doppler imager. Results ∆SBF was examined vs PRBC deformability, the transfusion‐induced increase in ∆Hct and the recipients’ SBF before transfusion (SBFB). ∆SBF elevated with increasing PRBC deformability, with a highly significant dependence, while its elevation with ∆Hct was much less significant. ∆SBF was inversely proportional to the SBFB. Conclusions This study provides, for the first time in humans, direct evidence that the deformability of transfused PRBC is a potent effector of transfusion outcome. Currently, PRBC are supplied primarily by the first‐in–first‐out criteria, while their functionality is ignored. The testing of PRBC hemodynamic quality would introduce a new paradigm into blood banking, which would contribute substantially to improving transfusion therapy.